2010
DOI: 10.1111/j.1095-8649.2010.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in the diet of pearly razorfish Xyrichtys novacula (Osteichthyes: Labridae)

Abstract: The diet of pearly razorfish Xyrichtys novacula, caught monthly along the shores of the Island of Lampedusa, appeared to be mainly composed of crustaceans, followed by colonial ascidians, molluscs and polychaetes. Among prey, sand dwellers and phanerogam-associated species were recorded. In winter months, the diet was characterized by a small number of prey items, dominated by colonial ascidians, while in spring and summer a wider prey array was recorded. Dietary indices show that X. novacula do not strictly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…March-April, July-August and October-November) (Ribera d 'Alcalà et al, 2004) while other important prey organisms, such as mysids and amphipods, proliferate from April to September (Sardà et al, 1999;Chimenz Gusso et al, 2001;Esposito et al, 2014). Similar considerations have also been pointed out in the Straits of Sicily (central Mediterranean), where benthic fishes such as Xyrichtys novacula exploit pelagic organisms in distinct periods, corresponding to the increase in secondary production after phytoplanktonic blooms (Castriota et al, 2010). The increase in benthivorous and planktivorous fishes recorded in our study area during early May and late June would therefore be justified by concomitant blooms of zooplankton and suprabenthic prey organisms.…”
Section: Discussionmentioning
confidence: 60%
“…March-April, July-August and October-November) (Ribera d 'Alcalà et al, 2004) while other important prey organisms, such as mysids and amphipods, proliferate from April to September (Sardà et al, 1999;Chimenz Gusso et al, 2001;Esposito et al, 2014). Similar considerations have also been pointed out in the Straits of Sicily (central Mediterranean), where benthic fishes such as Xyrichtys novacula exploit pelagic organisms in distinct periods, corresponding to the increase in secondary production after phytoplanktonic blooms (Castriota et al, 2010). The increase in benthivorous and planktivorous fishes recorded in our study area during early May and late June would therefore be justified by concomitant blooms of zooplankton and suprabenthic prey organisms.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies of labrid diets have focused on either single species (Gillanders, 1995; Denny & Schiel, 2001; Shepherd & Clarkson, 2001; Figueiredo et al , 2005; Castriota et al , 2005, 2010) or a group of species in the same habitat (Kabasakal, 2001; MacArthur & Hyndes, 2007; Morton et al , 2008). Certain studies have shown that the relative abundance of the prey taxa ingested by labrids tends to reflect the relative abundance of those prey in the environment (Deady & Fives, 1995; Shepherd & Clarkson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The dietary composition of many fish species, including those of labrids, has been shown to change during the year (Jones, 1988; Gillanders, 1995). This trend is conspicuous among those that feed on small prey, which have short life cycles and whose abundance thus peaks during a particular period of the year (Denny & Schiel, 2001; Castriota et al , 2010). Analyses of diets must also take into account the possibility that dietary composition can vary markedly among the various populations of a species, presumably in response to variations in the spatial availability of the different types of prey in the environment (Sarre et al , 2000; Chuwen et al , 2007; Duffy et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This could account for our finding that the diversity of the food types ingested by the black scorpionfish in the Pag Island was greater than that of the same species in the Split area. In general, variations by area in the studies on fish diet are commonly related to differences in availability of resources in each area [41,42]. The findings on dietary compositions emphasize that in two different areas that were the subject of the present study, S. porcus feeds on a wide variety of plant and animal taxa, as it does in areas elsewhere in the Mediterranean [6,[12][13][14].…”
Section: Discussionmentioning
confidence: 71%